2021
DOI: 10.1002/chem.202102918
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Ligand and Packing Effects on Slow Relaxation in an Isostructural Set of [Dy(H2dapp)X2]+ Single Molecule Magnets**

Abstract: We report three structurally related single ion Dy compounds using the pentadentate ligand 2,6‐bis((E)‐1‐(2‐(pyridin‐2‐yl)‐hydrazineylidene)ethyl)pyridine (H2dapp) [Dy(H2dapp)(NO3)2]NO3 (1), [Dy(H2dapp)(OAc)2]Cl (2) and [Dy(H2dapp)(NO3)2]Cl0.92(NO3)0.08 (3). The (H2dapp) occupies a helical twisted pentagonal equatorial arrangement with two anionic ligands in the axial positions. Further influence on the electronic and magnetic structure is provided by a closely associated counterion interacting with the centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Restricting the sums in Eq. 14 to a few modes, whose energy and coupling are left as adjustable parameters, it was shown that additional insights on spin relaxation can be obtained with respect to a fitting done with simple power laws ( 23 , 48 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Restricting the sums in Eq. 14 to a few modes, whose energy and coupling are left as adjustable parameters, it was shown that additional insights on spin relaxation can be obtained with respect to a fitting done with simple power laws ( 23 , 48 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…199 contains the frequency of the phonons contributing to relaxation and therefore is able to provide a clearer interpretation of relaxation experiments. Such approach has been successfully applied to a series of spin 1/2 systems [98,99,109,110].…”
Section: The Mechanism Of Spin-phonon Relaxation In Magnetic Moleculesmentioning
confidence: 99%
“…[5,7,12,13,15,22] There are two reviews: one is focused on elucidating the magnetic benefits and challenges of cooperativity within 3d-4f based coordination clusters of archetypical butterfly type, [21] and the other one highlights more generally the advancement of inorganic coordination chemistry by spectroscopy of isolated molecules in view of the applied methods and the achieved applications. [18] Three communications, [3,12,22] one concept article [8] and 17 full papers [1,2,[4][5][6][7][9][10][11][13][14][15][16][17]19,20,23] document and discuss particular 3MET species and their relevance for our understanding of the TM interactions within. A contribution on the development and application of a complete active space spin-orbit configuration interaction program designed for molecule magnets deserves special mention: this manuscript appears in a more specialized sister journal.…”
mentioning
confidence: 99%
“…The current special issue of Chemistry -a European Journal issue comprises 23 contributions in total, 17 of which stem from work that was conducted within the framework of the 3MET.de center, [1][2][3][4]6,[8][9][10][11]14,[16][17][18][19][20][21]23] and six from outside. [5,7,12,13,15,22] There are two reviews: one is focused on elucidating the magnetic benefits and challenges of cooperativity within 3d-4f based coordination clusters of archetypical butterfly type, [21] and the other one highlights more generally the advancement of inorganic coordination chemistry by spectroscopy of isolated molecules in view of the applied methods and the achieved applications.…”
mentioning
confidence: 99%